Effectiveness of Adjuvant Chemo- and Radiotherapy in Thymic Carcinoma Stage II: A Systematic Review and Meta-Analysis - Ahmad Nazzal MD; Josef Yayan MD, PhD; Christian Biancosino MD, PD; Seyed Vahid Tabatabaei MD; Khosro Hekmat MD (Cancer Control)
Background Thymic carcinoma is a rare tumor arising from the epithelial thymic tissue, yet among mediastinal tumors, it is the most common malignant entity. Thymic carcinoma often causes no symptoms and is incidentally discovered. Adjuvant radiotherapy is recommended, particularly in cases of incomplete resection and for stages III and IV, based on current guidelines and existing literature. In stage II (Masaoka-Koga system), the role of chemotherapy remains controversial, particularly in cases of incomplete resection. Therefore, this study aims to assess the effectiveness of adjuvant chemotherapy compared to adjuvant radiotherapy in the treatment of stage II (Masaoka-Koga system) thymic carcinoma after surgery. Methods A comprehensive literature search was conducted in the Embase, Cochrane Central Register of Controlled Trials (CENTRAL), and MEDLINE/PubMed databases for relevant studies published through April 30 th , 2023. Results The review identified a total of 101 studies in the Embase, Cochrane Library, and MEDLINE/PubMed databases. Of these, only eight retrospective studies met the inclusion criteria and were included in the meta-analysis. These eight studies encompassed a total of 323 patients with stage II (Masaoka-Koga system) thymic carcinoma, with an average patient age of 53.8 ± 5.0 years. There was no significant difference in the number of R0 resections between patients receiving adjuvant chemotherapy and those receiving adjuvant radiotherapy ( P = 0.82). Patients who received adjuvant radiotherapy had a higher rate of recurrence, but this difference was not statistically significant ( P = 0.93). The meta-analysis synthesized five-year overall survival data, with a combined hazard ratio (HR) of 0.881 (95% CI: 0.463 to 1.299), indicating no statistically significant difference between the treatment groups. Conclusions Although the results were not statistically significant, the findings suggest that adjuvant chemotherapy might be associated with a more favorable outcome for patients with stage II (Masaoka-Koga system) thymic carcinoma compared to adjuvant radiotherapy.